“Some Work of Noble Note”: Changes and Chances in Literary Pedagogy - Willett, Mischa (Christianity & literature, 2021)
English departments at Christian liberal arts institutions have faced a broadband array of economic and cultural challenges in recent years, some generated at the departmental or programmatic level and other imposed from without due to shifting generational commitments; thankfully that same regraded terrain has unearthed opportunities to remake ourselves, to renew our commitments to the college-level study of the good, the true, and the beautiful in literature.